The effect of persuasive communication on purchase decisions and Customer satisfaction in Sport Fashion products - Mar Astika, Nadia; Budianto, Heri (COMMICAST, 2025)
Fashion in Indonesia is currently experiencing a very exciting growth. E-commerce has been increasing Persuasive communication is one of the important strategies in influencing consumer behavior, especially in the process of making purchasing decisions and achieving customer satisfaction. Speaking of the fashion sports industry, intense competition demands the implementation of effective marketing communications to attract consumer attention while building customer loyalty, so as to provide strategic insights for brand managers in improving competitiveness and service quality. The aims to this study analyze the effect of persuasive communication on purchasing decisions for sports fashion products.  Quantitative research using the explanatory survey method. The research was conducted at Sogo Department Store outlets in Grand Indonesia from January to June 2024. The sampling technique used probability sampling and non-probability sampling with the number of samples used as many as 100 respondents. The independent variable in this study is persuasive communication, while the dependent variable is purchasing decisions and customer satisfaction. Univariate and bivariate data analysis. Statistical tests using product moment correlation test and multiple linear regression.  Regression tests show that persuasive communication has a significant effect on purchasing decisions (p-value 0.001; coefficient 0.364) and customer satisfaction (p-value 0.001; coefficient 0.222), so that each increase of one unit of persuasive communication increases purchasing decisions by 0.364 and customer satisfaction by 0.222. There is significance between the influence of persuasive communication and customer satisfaction on purchasing decisions for fashion sport products.